THE EFFECT OF CRITICAL PARAMETERS ON THE OIL SEPARATOR VESSEL (102D1) TO REDUCE THE VALUE OF FATTY ACID ESTER (FAE) IN THE GLYCERIN WATER PRETREATMENT UNIT AT PT. DOMAS AGROINTI PRIMA - Siswanto, Rudi; Salmyah, S; Harunsyah, H (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTGlycerin water produced from the hydrolysis process in the splitting column still contains impurities such as oil or fatty acids that are carried along with glycerin water or other impurities found in the raw oil itself such as solid particles and gum. Oil or fatty acids that are still present in glycerin water must be removed or lowered to the maximum permissible limit before further processing in glycerin evaporation units and glycerin distillation units. The quality standard set for glycerin water is the value of fatty acid ester (FAE) in glycerin water. Glycerin water will be treated first in the glycerin water pretreatment unit to remove the oil and fatty acid content. Oil separator vessel (102D1) is one of the tools in the glycerin water pretreatment unit, is one of the important ones to control in the glycerin water pretreatment unit. Where in this oil separator vessel there will be an initial separation between oil and fatty acid with glycerin water. Optimization of separation in oil separator will determine the decrease in FAE value in (102D1) treated glycerin water end product. Observations were made on the oil separator vessel, namely temperature and pH to see both parameters of this process against the decrease in the value of fatty acid ester, data collection for temperature and pH was carried out 3 times a day for 6 days for each still paremeter to determine the value of fatty acid ester. From the observed data on the oil separator device, there are two parameters that determine the separation of oil and fatty acid from glycerin water, namely temperature and pH. The results obtained that temperature and pH greatly affect the value of fatty acids, where the higher the temperature, the lower the FAE value, from the observation data the optimum temperature is 90 – 95 oC. pH also greatly affects the value of fatty acid ester after oil separator, where the clover's pH is low in its fatty acid ester value. From the observed data, the optimum pH is pH 2 – 3.5Keywords: Fatty Acid Ester, Oil Separator, Pretreatment Glycerin Water, pH, Temperatur